Colecta de semillas de Ilex paraguariensis, en yerbales antiguos de Paraguay (Journal on studies and research of academic knowledge, 2019)
The yerba mate (Ilex paraguariensis, Aquifoliaceae) is a specie of economic and cultural importance for Paraguay. The natural area of the yerba mate distribution is severely fragmented, so the natural populations have been reduced. Despite the importance of the species, Paraguay currently does not have a germplasm bank of yerba mate. At present, there are old cultivated that could be a genetic diversity reservoir, some of these old cultivated are being replaced or eliminated. With the objective to rescue this material, a possible source of genetic variability, seeds were collected from 207 plants, located in 16 old cultivated, with an age greater than 26 years, 15 of them located in Itapúa department and one in Caazapá department. This project being the first initiative to collect plant genetic resources of yerba mate from old cultivated plantations.
Keywords: germplasm collecting; yerba mate; genetic diversity; conservation